A Framework for IoT-Enabled Secure Access Using Face-Mask Detection - Sistu, Sri K H; Chadaram, P S S; Varma, A K; Gurala, C (2022 International Conference on Breakthrough in Heuristics And Reciprocation of Advanced Technologies (BHARAT), 2022)
Smart automation systems play a major role in enhancing secure access functionality under unique constraints such as - human test subjects can be in uniform, wear a face mask, carry a picture ID or for the first time we conjecture that some form of physical verification is indeed a routine for secure recognition besides the features such as a person's face biometric. In this paper, we propose a framework for smart phone activated secure access which can operate in closed indoor environment such as commercial, hospital, office complex. The mobile apps can advantage through IoT enabled edge server and cloud data services. In this paper we have shown an electronic system that performs mask detection in addition to the face biometrics required for monitoring human movement in a pandemic such as covid-19 or in highly sanitized spaces such as cooking area and clinical facilities. We use teachable machine for detection of face mask and user face. In the proposed solution a physical latch unlocks true positive events for detecting the genuine user's face and the mask.